Meropenem and piperacillin/tazobactam optimised dosing regimens for critically ill patients receiving renal replacement therapy - Roberts, Jason A.; Ulldemolins, Marta; Liu, Xin; Baptista, João P.; Bilgrami, Irma; Boidin, Clement; Brinkmann, Alexander; Castro, Pedro; Choi, Gordon; Cole, Louise; Waele, Jan J. De; Deans, Renae; et al. (Springer Nature, 2025)
Purpose: Optimal dosing of meropenem and piperacillin/tazobactam in critically ill patients receiving renal replacement therapy (RRT) is uncertain due to variable pharmacokinetics. We aimed to develop generalisable optimised dosing recommendations for these antibiotics.